Atypical presentation of an epidermal nevus in an unusual location. - Katike, P.; Badabagni, P.; Singh, S.; Mavoori, A.; Bhamidipati, H.S.; Gautam, A. (European Journal of Pediatric Dermatology, 2024)
The epidermal nevus usually begins in the first year of life without any gender predilection and is located more frequently on the head and neck, with different morphological characteristics depending on the predominant component. A case of epidermal nevus of the scrotum with cerebriform appearance was presented in a 15-year-old boy. The nevus was excised and the histological examination showed the characteristics of the epidermal nevus.